VD_FINDINFO Décision / 2014 / 1106 vom 16. Dezember 2014 - VD Tribunal cantonal (2014)
NON-LIEU, PLAINTE PÉNALE, CONTRAINTEDROIT PÉNAL, TENTATIVEDROIT PÉNAL, INJURE | 177 CP, 22 ad 181 CP, 30 CP, 310 CPP (CH)